Pelatihan Manajemen Keuangan Keluarga Bagi Anggota Aisyiyah Banjarmasin 9 Kota Banjarmasin - Emilia, Lea; Nikmah, Nailiya; Irwansyah, Rusman; Maharani, Sari Hepy (Politeknik Negeri Banjarmasin, 2019)
The diverse needs of life need to be in the management of family finances, because there can be expenditure more than the amount of income. Lifestyle changes can be a trigger for increased family spending. The purchase of unneeded secondary items can also increase the amount of expenditure. Similarly, the acquisition of consumptive assets or productive asset through an increase in the amount of debt requires the calculation of the portion of debt in accordance with the income. In addition, unexpected events in the family such as the presence of sick family members or payment transactions of children's education funds requiring substantial funds require good management by mothers as household finance managers.The purpose of this community service is to provide training on the management of family finances to Aisyiyah members of Banjarmasin 9 Banjarmasin city. The benefit of this activity for the partner's devotion is to provide knowledge on how to plan the expenditure of family finances, implementation of family financial management and assessment/ supervision of family finances. Keywords: Familiy financial management, training, Aisyiyah Banjarmasin 9 Banjarmasin City